Catheter ablation of persistent atrial fibrillation with heart failure improves hemodynamic status without deteriorating renal function in the elderly. (3rd October 2022) - Okahara, A; Kawai, S; Tokutome, M; Matsuura, H; Noma, A; Hara, A; Nakashima, H; Watanabe, T; Sakemi, T; Okabe, K; Matsukawa, R; Masuda, S; et al.
Abstract: Background/Introduction: Atrial fibrillation (AF) and heart failure (HF) frequently coexist in the elderly people, leading to worse clinical outcomes. HF with preserved ejection fraction (HFpEF) is the most common form of HF in the elderly, particularly in women, associated with AF. Ablation of AF in younger patients with HF with reduced EF (HFrEF) has become an established treatment option. However, clinical impact of ablation for persistent AF accompanying with HF in the elderly remains unclear. Purpose: This study aimed to evaluate the effect of catheter ablation of persistent AF with heart failure in the elderly. Methods: Consecutive 70 patients who underwent catheter ablation of persistent AF accompanying with HF (NYHA class> II, mean LVEF 51.7%) in our institution were retrospectively analyzed with regards to their 1-year clinical outcomes, HF markers such as BNP, renal function and transthoracic echocardiographic findings. Patients were dichotomized by age of 75-year-old (31 elderly vs 39 younger subjects) and separately analyzed. Results: Mean age of the studied population was 70.5 year-old; 79.6±3.8 in the elderly group and 63.2±8.5 in the younger group. The elderly patients were more frequently females (45% vs 21%). Longstanding persistent AF was observed in 32% in the elderly and 28% in the younger group. Circumferential pulmonary vein isolation (PVI) was performed in all patients, with additional ablations of liner lesions and/or non-PV foci as needed. PVI alone was observed in 54.8% in the elderly and 41% in the younger group. There were no serious complications associated with the procedure. During 1 year after ablation, recurrence of AF was observed in 15 patients [6/31 (19%) in the elderly, 9/39 (23%) in the younger]. Readmission due to HF was observed in only 1 patient in the elderly and 2 patients in the younger group (3% vs. 5%, respectively). Cardiovascular events were observed in 3 patients [2/31 (6%) in the elderly, 1/39 (3%) in the younger], but there was no death. The BNP level as well as the NYHA class significantly decreased at 1-year follow-up compared to baseline in the both groups (Figure A and B). There was no change in serum creatinine level in the both groups (Figure C). The left atrial dimension and the LA volume index decreased at 1-year follow-up in the both groups (Figure D and E). The LVEF improved only in the younger group (Figure F). Conclusions: Ablation of persistent AF in the elderly with HF (mostly with preserved EF) was associated with hemodynamic and functional improvements without deteriorating renal function in a mid-term, which was mostly comparable to the results in the younger. Funding Acknowledgement: Type of funding sources: None.